AESTHETIC VALUE: ATTACHMENT TO DIGITAL EXPERIENCE AND REAL-LIFE EXPERIENCE: Received: 21st February 2023; Revised: 24th May 2023, 05th June 2023; Accepted: 13th June 2023 - Sirikhvunchai, Natcha (PEOPLE: International Journal of Social Sciences, 2023)
The purpose of this academic article was to proof the phrase “Phygital Experiences” by present the merging of digital experiences and real-life experiences in the view of value and aesthetics through 5 roles of digital approach, namely, the role of digital age towards education, the role of digital age towards work, the role of digital age towards economy, the role of digital age towards art and culture, and the role of digital age towards tourism. The study results revealed that technological evolution brings about new forms of interaction that people across the world consume and treat each other. Though digital experience enables people to have comfort, access information and communicate with each other more easily, people do not have profundity and meticulousness to understand experience. On the contrary, real-life experiences offer more experiences of participation in terms of sensory perception or emotional perception. However, they are unable to offer borderless connection and data accessibility as comfortable as digital experiences. Therefore, it can be said that digital experiences and real-life experiences cannot be separated since both of them can fulfill human’s good experiences in a different way, making humans feel fulfilled and enjoyable while they can admire things surrounding themselves. Humans receive benefits from technologies while connecting to the world they can touch.